DETERMINAN STRUKTUR MODAL PADA SEKTOR KEUANGAN YANG LISTING DI BURSA EFEK INDONESIA - SUKASIH, NI KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 2 (2011), 2011)
The purpose of this study is to investigate the influence of partial and simultaneous determinants of capital structure, including the cost of interest, dividend policy, size of the company, return on equity (ROE) and return on investment (ROI) and taxes paid in the financial sector. This research is limited to banking and lease corporation listing on the Indonesia Stock Exchange. Hypothesis is tested using multiple regression analysis and chow test. The results show that banking interest expense, dividend policy, company size, ROE, ROI and paid taxes simultaneously affect capital structure with adjusted R square value of 0.298 (29.8%) which means that 29.8% of the variation in capital structure can be explained by the six independent variables, interest, dividend policy, company size, ROE, ROI and taxes while the remaining 70.2% is explained by other variables. Results of the lease obtain the adjusted R square of 0.353 (35.3%) meaning that variation in capital structure can be explained by the six independent variables, while the remaining 64.7% is explained by other variables.
Keywords: banking, determinant, capital structure, financial sector